2016
DOI: 10.3892/br.2016.805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on myocardial ischemia-reperfusion injury in rats with type-2 diabetes mellitus

Abstract: Abstract. The current study aimed to examine the effects of propofol on myocardial ischemia-reperfusion injury (MIRI) in rats with type-2 diabetes mellitus (T2DM) and to assess the role of inflammatory mediators. Fifty healthy male adult Sprague-Dawley rats were randomly divided into the sham, ischemia-reperfusion (IR), IR plus low, middle and high-dose (6, 12 and 24 mg/kg/h, intravenous) propofol groups. The rats of all the groups were fed a high-sugar and high-fat diet for 8 weeks and streptozotocin (30 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…The underlying radio-protective mechanisms were explored further, and consistent with previous studies, 7,17,18 propofol decreased the ROS levels in LSKs and HPCs. It has been reported that propofol can alleviate transplanted liver damage 15 through the Nrf2 pathways.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The underlying radio-protective mechanisms were explored further, and consistent with previous studies, 7,17,18 propofol decreased the ROS levels in LSKs and HPCs. It has been reported that propofol can alleviate transplanted liver damage 15 through the Nrf2 pathways.…”
Section: Discussionsupporting
confidence: 61%
“…8 Propofol can also decrease ROS levels in a myocardial ischemia-reperfusion injury model in vitro and alleviate myocardial injury caused by postreperfusion. 17,18 Moreover, propofol attenuates intestinal ischemia-reperfusion injury by scavenging ROS, 7 improves Parkinson's disease by activating antioxidant enzyme activity, and inhibits lipid peroxidation in heart, liver, kidney, and lung tissue. 19 In summary, the anti-oxidative effect of propofol protects against a variety of tissue damage caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the model of acute myocardial ischemia performed by coronaries ligation was successfully established. Similar results were found in previous works of rabbits and other species [ 2 , 4 , 29 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that propofol-induced Nrf2/HO-1 expression is increased in the early stage of reperfusion at penumbra region. Wang et al reported that administration of propofol ameliorated the cardiac function of rats at 2 h after reperfusion [ 23 ]. It is presumed that the expression of Nrf2 and its downstream enzyme including HO-1 are elevated in the early reperfusion stage and contribute to restoration of cardiac function.…”
Section: Discussionmentioning
confidence: 99%